Parâmetros ecofisiológicos de Poincianella pyramidalis (Tul.) L. P. Queiroz e sua relação com a variabilidade temporal das chuvas em áreas do Semiárido paraibano - Lima, Cosmo Rufino de (2014)
The catingueira [Poincianella pyramidalis (Tul.) L. P. Queiroz] is a tree species endemic to the Caatinga, quite explored for their potential timber, forage and pharmacological. Given the relevance of its importance, the research aimed to: (i) characterize the phenophases of P. pyramidalis, and its relation to the distribution of rainfall pulses; (ii) evaluate the physiological quality of seeds among individuals of P. pyramidalis through physiologic tests; (iii) determine the physiological maturation of the seeds and (iv) evaluate the potential for dry matter yield due to leaf abscission and its relation to the temporal distribution of rainfall. First 32 individuals of P. pyramidalis were selected, at Açude Farm, the city of Soledade-PB, as evaluation method using the percentage of intensity Fournier and activity index. To evaluate the variability between individuals and determination of the maturity, individuals catingueira fruits were collected and referred to the Laboratory of Seed Analysis (CCA/UFPB), for seed extraction and evaluation of physical and physiological variables. For quantification of dry matter due to leaf abscission catingueira, the work was conducted at the Experimental Station of São João do Cariri-PB, whinch where distributed under the canopy of 15 plants four collectors in the north-south and east-west direction. Thus, it was found that the the intensity and duration of phenophases in Poincianella pyramidalis depend on the amplitude and frequency of pulses of rainfall during the rainy season; the accelerated aging test, used in the traditional method, the period of 24 hours and at a temperature of 41 ºC shows the test vigor to be more efficient in evaluate the physiological potential of the seeds of P. pyramidalis; that conditions Soledade city-PB, for P. pyramidalis the point of physiological maturity occurs at 125 days after anthesis, when seeds reach maximum dry mass accumulation, and the harvest is reached between 130-135 d.a.a.; the rapid senescence and leaf fall of P. pyramidalis are due to interpulse precipitation and strong reduction of water availability in the soil; during the period of abscission, the incrise of contribution of leaves is highly dependent on the quantity of rainfall between years.